Decision making : a case study of the decision to raise the bank rate in September 1957 - Chapman, Richard A. (London ; New York : Routledge & K. Paul ; Humanities P., 1968)
This monograph contains a brief general introduction indicating the significance of the decision of the tribunal in relation to bank rate, legal responsibility and economic situation.
Bibliography: p. 115-118.
sju 25/01/2019
Loans
Keywords: Interest rates; Decision making